Blockchain-based voluntary carbon market: strategic insights into network structure - Bassi, Eleonóra; Lustenberger, Michael; Letina, Srebrenka (Frontiers in Blockchain, 2025)
This research examines the structure of blockchain-based voluntary carbon market (VCM) and the factors shaping their formation. Conducted as part of the 2023–2025 Innosuisse project 104.664 IP-EE, it aims to provide insights to support participants in strategic positioning within the network. To our knowledge, this is one of the first empirical attempts to map the blockchain-enabled VCM ecosystem with social-network analysis, thereby extending digital-transition research into the climate-finance domain. Specifically, the study focuses on three exploratory aims: identifying the network position of key participants, evaluating the influence of blockchain platform affiliation on collaboration, and analyzing the relationship between standardization methods and network positioning. Using network analysis, the study categorizes participants like project owners, certification bodies, blockchain platforms, and carbon credit marketplace into distinct roles such as key hubs, strategic bridges, local connectors, and peripheral nodes. Participants using the same blockchain platform exhibit a moderate clustering tendency, suggesting shared infrastructure plays a role in fostering partnerships. Additionally, the choice of standardization methods for carbon credits correlates with specific network positions. These findings offer a structure-based view of how technical design choices may redistribute influence across the market–an issue of growing interest as regulators and standards bodies debate digital registry architectures. By uncovering these dynamics, the study emphasizes the importance of strategic positioning within blockchain-based VCMs. Native tokenization strategies are shown to simplify supply chains, while the decentralized ecosystem fosters diverse approaches to collaboration. The conceptual framework may be transferable to other emerging green-finance networks, providing a springboard for comparative and longitudinal analyses.